Geochemistry and Geochronology data for Great Slave Lake shear zone supracrustal samples - Cutts, Jamie A.; Dyck, Brendan (Zenodo, 2021)
Supplementary tables include bulk compositions used for phase equilibria modelling (Table S1), garnet trace-element data (Tables S2-S3), garnet Lu-Hf isotopic data (Table S4), monazite (Table S5) and zircon (Table S6) U-Pb and trace-element data, and laser ablation-inductively coupled plasma-mass spectrometry instrument settings and metadata (Table S7).